Research on the Influence of Load Difference for Photovoltaic Micro-grid System Performance (Journal of Solar Energy Research Updates, 2022)
Abstract: In this paper, make use of PVSOL software studied the generation performance and Economic benefits of PV system at various inclinations. And then analyzed residential load, industrial load and commercial load system performance and self-sufficiency under different battery capacity. The results show that for Shanghai area, when the inclination angle of PV panel is about 23o, the annual total power generation of PV system reaches the maximum. The self-sufficiency rate of PV systems with industrial load is higher than commercial load, and the self-sufficiency rate of PV systems with residential load is the lowest. The self-sufficiency rate of PV systems with batteries are higher than PV systems without batteries, and the increment of installation power can increase self-sufficiency rate of the PV system.